Characterization of hepatitis B virus in Amerindian children and mothers from Amazonas State, Colombia (2017)
ABSTARCT: Hepatitis B Virus (HBV) infection is a worldwide public health problem. In the 1980's a highly effective and safe vaccine against HBV was developed, although breakthrough infection still occasionally occurs because of the emergence of escape mutants. The aim of this study was to identify HBV genotypes and escape mutants in children and their mothers in Amerindian communities of the Amazonas State, Southern Colombia. METHODS: Blood specimens collected from children and mothers belonging to 37 Amerindian communities in Amazonas state, were screened for HBsAg and anti-HBc using ELISA. The partial region containing the S ORF was amplified by nested PCR, and amplicons were sequenced. The phylogenetic analysis was performed using the MEGA 5.05 software. RESULTS: Forty-six children (46/1275, 3.6%) and one hundred and seventy-seven mothers (177/572, 30.9%) were tested positive for the anti-HBc serological marker. Among them, 190 samples were tested for viral genome detection; 8.3% (2/31) serum samples obtained from children and 3.1% (5/159) from mothers were positive for the ORF S PCR. The predominant HBV genotype in the study population was F, subgenotype F1b; in addition, subgenotype F1a and genotype A were also characterized. Two HBV escape mutants were identified, G145R, reported worldwide, and W156*; this stop codon was identified in a child with occult HBV infection. Other mutations were found, L109R and G130E, located in critical positions of the HBsAg sequence. CONCLUSIONS: This study aimed to characterize the HBV genotype F, subgenotypes F1b and F1a, and genotype A in Amerindian communities and for the first time escape mutants in Colombia. Further investigations are necessary to elucidate the frequency and the epidemiological impact of the escape mutants in the country.